Status of Human Resources: Implications for the Implementation of Upper Basic of the Universal Basic Education (UBE) Programme in Bayelsa State of Nigeria - G.B. Inyang; A.O. Akinbobola; I.B. Ado (University of Sofia, 2010)
This study investigates the status of human resources in Bayelsa State of Nigeria and its implications for the implementation of upper basic of the Universal Basic Education (UBE) programme. A total of 181 teachers were involved in the study. The results of the study show that there are qualified human resources for the implementation of upper basic of the UBE programme in Bayelsa State of Nigeria but they are inadequate in all the three basic subjects (English Language, Mathematics and Integrated Science). Also, there is no significant difference in the availability and adequacy of human resources in the three subjects. It is recommended that adequate human resources should be provided by the government for effective teaching and implementation of the UBE programme.